Staring down the wolf : 7 leadership commitments that forge elite teams - Divine, Mark (St. Martin's Press, 2020)
"A leadership book by former Navy SEAL and New York Times bestselling author Mark Divine, focused on harnessing the principles of purpose and discipline in life to achieve success. What does it take to command a team of elite individuals? It requires a commitment to seven key principles: Courage, Trust, Respect, Growth, Excellence, Resiliency, and Alignment. All of these are present in an elite team which commits to them deeply in order to forge the character worthy of uncommon success. Retired Navy SEAL Commander, Entrepreneur and New York Times Best Selling Author Mark Divine (founder of SEALFIT, NavySeal.com, and Unbeatable Mind) reveals what makes the culture of an elite team, and how to get your own team to commit to serve at an elite level. Using principles he learned on the battlefield, training SEALs, and in his own entrepreneurial and growth company ventures, Mark knows what it is to lead elite teams, and how easily the team can fail by breaching these commitments. Elite teams challenge themselves to step up everyday to do the uncommon. Developing the principles yourself and aligning your team around these commitments will allow you to thrive in VUCA (volatility, uncertainty, complexity, ambiguity) environments, no matter your background or leadership experience. Drawing from his twenty years leading SEALs, and twenty five years of success and failure in entrepreneurship and ten years coaching corporate clients, Mark Divine shares a very unique perspective that will allow you to unlock the tremendous power of your team"--